Efficiency of incentives to jointly increase carbon sequestration and species conservation on a landscape - Nelson, Erik (National Academy of Sciences, 2008)
We develop an integrated model to predict private land-use decisions in response to policy incentives designed to increase the provision of carbon sequestration and species conservation across heterogeneous landscapes. Using data from the Willamette Basin, Oregon, we compare the provision of carbon sequestration and species conservation under five simple policies that offer payments for conservation. We evaluate policy performance compared with the maximum feasible combinations of carbon sequestration and species conservation on the landscape for various conservation budgets. None of the conservation payment policies produce increases in carbon sequestration and species conservation that approach the maximum potential gains on the landscape. Our results show that policies aimed at increasing the provision of carbon sequestration do not necessarily increase species conservation and that highly targeted policies do not necessarily do as well as more general policies.